Naive freedom. Against the compatibilist perspectivism of Spinoza and Dennett - Ibañez Blancas, Franklin Ernesto (2024)
This paper criticizes a kind of compatibilism: the perspectivism, which can be tracked fromBaruch Spinoza –controversially in his case in modernity to Daniel Dennett in now days. This compatibilism states reality can be expressed or read from several perspectives, which do not cancel each other, but coexist. From one of those perspectives, determinism is a logical conclusion. From other perspective, at the same time, freedom exists plausibly. The paper argues that both authors subscribe an ontology  a materialism with a unique substance which entails the possibility of a privileged deterministic perspective that invalidates freedom.